Strategies for successful writing : - Reinking, James A. (Pearson Prentice Hall, 2005)
This best-selling text combines three books-a rhetoric, a research guide, and reader-into one convenient and flexible teaching tool while offering students an exceptional value. Also available in an alternate versionwith a Handbook section.